The Diamond I13 full-field transmission X-ray microscope: a Zernike phase-contrast setup for material sciences. (December 2020) - Storm, Malte; Döring, Florian; Marathe, Shashidhara; David, Christian; Rau, Christoph
Abstract : The I13 transmission X-ray microscope at Diamond Light Source (DLS) has been designed to cover a broad range of energies and field of views. The beamline operates on an undulator source, and a multilayer monochromator can be used to work at a larger bandwidth to enable faster acquisitions. The experimental design includes large working distances for the optics to allow installing in situ sample environments. This paper presents the current state of the experimental system and shows some of the latest results.